2009
DOI: 10.1210/en.2008-1247
|View full text |Cite
|
Sign up to set email alerts
|

The Differences in Neuroprotective Efficacy of Progesterone and Medroxyprogesterone Acetate Correlate with Their Effects on Brain-Derived Neurotrophic Factor Expression

Abstract: Whereas hormone therapy is used for the treatment of menopausal symptoms, its efficacy in helping reduce the risk of other diseases such as Alzheimer's disease has been questioned in view of the results of recent clinical trials that appeared inconsistent with numerous basic research studies that supported the beneficial effects of hormones. One possible explanation of this discrepancy may lie in the choice of hormone used. For example, we and others found that progesterone is neuroprotective whereas medroxypr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
60
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(66 citation statements)
references
References 27 publications
3
60
1
Order By: Relevance
“…In addition, we also observed that PROG preserves the microtubule-associated protein 2 (MAP2) immunostaining in deafferentiated motoneurones, which may help to recover cytoskeleton organization [5] . Collectively, our results and those from a recent report [7] suggest that PROG-induced BDNF expression correlates with its neuroprotective effects and may help to understand the potential role of PROG to support and sustain normal cellular function after SCI.…”
Section: Neuroprotective Effects Of Progesterone After Spinal Cord Insupporting
confidence: 75%
“…In addition, we also observed that PROG preserves the microtubule-associated protein 2 (MAP2) immunostaining in deafferentiated motoneurones, which may help to recover cytoskeleton organization [5] . Collectively, our results and those from a recent report [7] suggest that PROG-induced BDNF expression correlates with its neuroprotective effects and may help to understand the potential role of PROG to support and sustain normal cellular function after SCI.…”
Section: Neuroprotective Effects Of Progesterone After Spinal Cord Insupporting
confidence: 75%
“…PROG also has anti-inflammatory properties, and its action reduces the inflammatory response following brain damage [40,41]. By the activation of nuclear receptors, PROG increases the levels of brain-derived neurotrophic factor [42], a neurotrophic factor involved in neuroprotection and in maintaining neuron function [43]. PROG increases the expression of the mitochondrial antiapoptotic protein Bcl-2 [44] and was reported to decrease oxidative stress by increasing the levels of endogenous antioxidants such as glutathione, superoxide dismutase, and catalase [45].…”
Section: Discussionmentioning
confidence: 99%
“…In our recent publication, we observed norgestrel-mediated induction of bFGF, a neurotrophic factor repeatedly associated with protection from lightinduced photoreceptor degeneration, in the retina. This result is not unprecedented in neuronal tissue, induction of BDNF expression has been observed in the CNS in response to progesterone [17]. Therefore, induction of neurotrophic factors could account for some of the potent pro-survival properties of norgestrel, complementing the growth factor-based therapies that are currently under development for the treatment of retinal disease.…”
Section: Progestogens As Modulators Of Neuronal Survivalmentioning
confidence: 99%